Patterns in spiritual awakening: A study of Augustine, Coleridge and Eliot - Shafik, Lucy (AUC Knowledge Fountain, 2017)
My thesis explores the role of the self in spiritual narratives, adopting the philosophical perspectives of Plato, Aristotle, and Kierkegaard as modes of apprehending the reader's inward response to literature. I examine patterns of spiritual awakening in St. Augustine's Confessions, Coleridge's "The Rime of the Ancient Mariner", and T. S. Eliot's The Family Reunion, tracing and retracing phases in the protagonist's life, which lead to a crucial moment of conversion. I attempt to show how each character's experience acquires spiritual meaning on the basis of transformative insights and demonstrates its potential to shape the self. The purpose of the thesis is to allow the religious point of view to cast light on secular literature and to address various ways of approaching religious truths on a textual basis. In offering a religious response to secular spheres of culture, including art and philosophy, the thesis indicates how theology provides insights into literary texts that are concerned with ultimate meaning.